Реконструкція житлового фонду в Україні: техніко-економічний аспект - Молодід, О. О.; Молодід, О. С. (Ways to Improve Construction Efficiency, 2014)
The necessity of reconstruction of housing in Ukraine was grounded. The technical and economic characteristics of this type of construction activity were established. The kinds of reconstruction, which used more often, were identified. The main sources of funding for the reconstruction of housing were describes. The main technical requirements for the process of reconstruction were analyses.